2015
DOI: 10.1111/jgh.12978
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of cryptogenic compared with non‐cryptogenic cirrhosis: A retrospective cohort study

Abstract: Cryptogenic cirrhosis is associated with a longer duration of hospitalization compared with non-cryptogenic cirrhosis at an early stage of the disease. This difference is due to a greater burden of non-liver-related complications in the former.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The stringent definition of diabetes by universal biochemical screening of all undiagnosed cases was used in 91% of studies. The remaining studies reported that the diagnosis was made by either laboratory or current treatment for diabetes, suggesting that undiagnosed cases of DM may still have been overlooked.…”
Section: Resultsmentioning
confidence: 99%
“…The stringent definition of diabetes by universal biochemical screening of all undiagnosed cases was used in 91% of studies. The remaining studies reported that the diagnosis was made by either laboratory or current treatment for diabetes, suggesting that undiagnosed cases of DM may still have been overlooked.…”
Section: Resultsmentioning
confidence: 99%
“… 21 A majority of patients admitted to our ward for cirrhosis and its complications had cryptogenic cirrhosis, which is due to MASLD in most cases. 22 Similarly, cryptogenic cirrhosis as the etiology of hepatocellular carcinoma (HCC) cases seen in our center has more than doubled from 16% to 34% (not including 7% with established diagnosis of MASH) between the time periods of 2006–2009 and 2011–2014. 23 In the United States, MASH has become one of the leading causes of adult liver transplantation and among patients with HCC undergoing liver transplantation.…”
Section: Epidemiology Natural History and Burden Of Diseasementioning
confidence: 89%
“…Second, we found that non-cryptogenic LC was significantly associated with worse outcomes in patients after a 1-MV than cryptogenic LC (AHR = 1.43, 95%CI: 1.32-1.54). In contrast, one retrospective Malaysian cohort study[ 20 ] reported, after comparing the clinical outcomes in 94 cases cryptogenic LC and 207 cases of non-cryptogenic LC, cases that there was no significant difference in mortality between these two groups; however, the sample in that study was relatively small. A Japanese study[ 25 ], which compared 68 patients with cirrhotic non-alcoholic steatohepatitis (NASH) and 69 with HCV-induced LC, found that the 5-year survival rates and liver-related mortality were not significantly different in the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to viral hepatitis- and alcohol-related LC, cryptogenic cirrhosis, which is defined as LC that cannot be explained by conventional clinical, laboratory, or histological findings[ 15 , 16 ], is becoming increasingly prevalent in Asia[ 17 - 19 ]. The clinical manifestations and outcomes of LC and cryptogenic LC are different[ 20 ]. Thus, we also investigated whether the effects of non-cryptogenic LC and cryptogenic LC on the patients requiring 1-MV are different.…”
Section: Introductionmentioning
confidence: 99%